An exploration of the development of resilience in student midwives. (2nd June 2021) - Williams, Jacqui; Lathlean, Judith; Norman, Kay
Abstract : Student midwives have to complete a demanding programme to become a midwife, and therefore it is questioned whether they need resilience to be successful. The study's aims were to explore whether resilience developed in one cohort of 25 undergraduate student midwives and what the concept of resilience meant to them. This study adopted a longitudinal case study approach in one Higher Education Institution in England during the first 18 months of their programme. The study used Wagnild and Young's (1993) (updated 2015) True Resilience Scale©, administered on three occasions. Additionally, four focus groups were conducted twice and six participants were involved in one-to-one interviews to explore issues raised in the focus group. SPSS Pairwise comparisons revealed that there were significant differences in True Resilience Scale© scores between the first and the second completion ( p =0.034), and time one and time three ( p =0.002); there were no significant differences between time two and time three ( p =1.0). In this cohort of student midwives, the scale showed that the majority had developed their resilience during the study and this was supported in what the students reported. A conceptual model, which defines resilience for student midwives, is presented to strengthen how resilience can be supported and developed.